IbM for Increasing Bread Business “Bite Me” and “Dapoer Teh Widia” Kejuron Village, Madiun City - Agus Prasetya; Beni Dwi Komara; Ani Anjarwati (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
The “Bite Me” and “Dapoer Teh Widia” bakery businesses have considerable marketing potential, operating in the Kejuron Village area, Madiun City. The problems faced at this time are not having a dough making machine so that it is less smooth and the process of making bread is quite long. This business also lacks understanding of business financial management, and online marketing methods to develop a business. These problems make their businesses unable to meet market demand, difficult to access capital and the acceleration of business development is not as expected. Recognizing the problems faced by partners, community service activities were carried out to improve the performance of the two partners. The method used is in the form of 1) Providing Mixer Machine assistance with a capacity of 25 kg. 2). Training to increase the ability to make business and business risk accounting 3). Improved ability to market online. The results that have been achieved are the procurement of production equipment that has been planned even with the existing budget more production equipment can be fulfilled, there is a change in behavior to use business bookkeeping that was previously unknown and after the training there is a desire and ability to market online. All of this has an impact on increasing the quantity and quality of production which also significantly increases the market and partners' income.